Penerapan Metode Role Play untuk Meningkatkan Keaktifan Belajar Pendidikan Agama Katolik di SMPN 3 Tujuh Belas - Pasifikus Pasifikus; FR Wuriningsih (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to examine the effectiveness of the role-play learning method in increasing student learning activeness and engagement in the subject of Catholic Religious Education. The background of this research is the consistently low level of student participation and engagement during classroom learning, particularly in expressing religious values, responding thoughtfully to questions, and actively participating in discussions. This classroom action research was conducted in two cycles involving students of Grade VII at SMP Negeri 3 Tujuh Belas, Bengkayang. The research method employed consists of four stages: planning, action, observation, and reflection in each cycle, ensuring systematic implementation. Data were collected using observation sheets, detailed student activity assessments, and reflection notes from both students and teachers. The findings are expected to demonstrate that the role-play method encourages students to be more active, expressive, confident, and participatory in all learning activities. The implications of this research emphasize the critical importance of interactive, student-centered learning models in enhancing classroom engagement, strengthening the internalization of religious values, fostering critical thinking, and improving overall learning dynamics within the Catholic Religious Education curriculum.